Patterns of Relationship between Servant Leadership, Decision-Making, and Teachers' Professional Commitment in Educational Governance - Nurhayati; Rita Retnowati; Griet Helena Laihad (Candradimuka: Journal of Education, 2026)
Teachers' professional commitment plays a crucial role in strengthening educational governance and improving the quality of educational services. However, efforts to enhance teachers' professional commitment require an understanding of the organizational factors that contribute to its development. This study aims to analyze the relationship between servant leadership, decision-making, and teachers' professional commitment in the context of educational governance. This study employed a correlational survey method with a quantitative approach. Quantitative data were collected through questionnaires administered to 178 full-time teachers from private vocational high schools in Depok City, selected using a proportional random sampling technique. The instrument measured servant leadership, decision-making, and teachers' professional commitment. Quantitative data were analyzed using descriptive statistics and path analysis. The results showed that servant leadership had a positive and significant influence on teachers' professional commitment (β = 0.154; p = 0.043) and decision-making (β = 0.188; p = 0.014). Decision-making also showed a positive and significant influence on teachers' professional commitment (β = 0.236; p = 0.001). Furthermore, decision-making significantly mediated the relationship between servant leadership and teachers' professional commitment (indirect effect = 0.068; Z = 2.492; p = 0.013). This finding suggests that servant leadership contributes to strengthening teachers' professional commitment, both directly and indirectly, through improved decision-making. This study highlights the importance of encouraging servant-oriented leadership practices and participatory decision-making processes as strategic approaches to enhancing teacher professionalism and promoting effective educational governance.